Role of nanosilica localization on morphology development of HDPE/PS/PMMA immiscible ternary blends - Z. Javidi; Z. Tarashi; A. Rostami; H. Nazockdast (eXPRESS Polymer Letters)
In this work, we studied the parameters affecting the localization of hydrophobic nanosilica particles and its impact on morphology development of polyethylene/polystyrene/poly (methyl methacrylate) (HDPE/PS/PMMA) ternary blends, which originally have a thermodynamically preferred core–shell type morphology, by means of a combination of rheology and electron microscopy. An attempt was also made to compare the experimental results with thermodynamic predictions. The ternary blend samples with the same blend ratio but varying in nanosilica loadings were prepared by melt compounding using a laboratory internal mixer. It was demonstrated that the nanosilica localization which could be controlled by the sequence of feeding, would play a significant role in determining the morphology development of the nanofilled ternary blend samples. It was shown that in contrary to thermodynamic prediction of a core shell morphology for the nanofilled samples, the highly enhanced melt elasticity of nanosilica filled polystyrene phase did not allow the PS phase to form a complete encapsulating shell.